STIGMATIZATION RADICAL OF PESANTREN AND PUBLIC ACCEPTANCE OF ISLAMIC BOARDING SCHOOLS IN WEST SUMATRA - Fahmi, Reza; Aswirna, Prima; Fahmi, Farah Audi; Fahmi, Danial Muhammad (Proceeding of International Conference on Islamic Education (ICIED), 2022)
This study aims to: (1) Obtain a picture of radical stigmatization in Islamic boarding school education. (2) Public acceptance of pesantren as an Islamic educational institution (3) Testing the relationship between radical stigmatization and community acceptance of pesantren. The research uses a quantitative approach. The population in this study is the people of the city of Padang who live close to Islamic boarding schools. As for their number, it is mostly 2587 people. Meanwhile, the sample in this study was 364 people using the Slovin formula. Sampling is carried out in a simple random manner, with a stratified random sampling approach. The collection and data were carried out using psychological scales, interviews, and observations. Data analysis techniques use simple regression. The results of this study found that: (1) Stigmatization of Islamic boarding schools is relatively high among members of the community. This is built on empirical opinions and studies amid a society that finds the existence of alleged radicalism in Islamic educational institutions, including Islamic boarding schools. (2) Public acceptance of Islamic boarding schools is relatively high. This means that people still believe that pesantren is an Islamic educational institution that can still be trusted to send their children to school. (3) This study found there was no significant relationship between radical stigmatization and community acceptance of Islamic boarding schools. This means that although some studies lead to evidence of alleged radicalism in the world of Islamic education, including Islamic boarding schools. Even so, the public's interest in accepting pesantren as an educational institution that is a reference for learning among their children is also high. So people still choose pesantren as an alternative educational institution for the education of their children.